Parsing preferences and individual differences in nonnative sentence processing: Evidence from eye movements. (January 2021) - Cheng, Yesi; Rothman, Jason; Cunnings, Ian
Abstract: Using both offline and online measures, the present study investigates attachment resolution in relative clauses in English natives (L1) and nonnatives (L2). We test how relative clause resolution interacts with linguistic factors and participant-level individual differences. Previous L1 English studies have demonstrated a low attachment preference and also an "ambiguity advantage" suggesting that L1ers may not have as strong a low attachment preference as is sometimes claimed. We employ a similar design to examine this effect in L1 and L2 comprehension. Offline results indicate that both groups exhibit a low attachment preference, positively correlated with reading span scores and with proficiency in the L2 group. Online results also suggest a low attachment preference in both groups. However, our data show that individual differences influence online attachment resolution for both native and nonnatives; higher lexical processing efficiency correlates with quicker resolution of linguistic conflicts. We argue that the current findings suggest that attachment resolution during L1 and L2 processing share the same processing mechanisms and are modulated by similar individual differences.